1987
DOI: 10.3406/bulmi.1987.7993
|View full text |Cite
|
Sign up to set email alerts
|

A TEM study of lattice defects in naturally and experimentally deformed orthopyroxenes

Abstract: Divers OPX provenant de roches de haut grade métamorphique ou de péridotites ont été étudiés par microscopie électronique en transmission analytique. Les structures de défauts observées ont été comparées à celles produites par des déformations expérimentales (fluage à pression atmosphérique et déformation sous pression de confinement solide). Ces essais ont été réalisés sur des monocristaux orientés pour promouvoir les systèmes de glissement (100) [001], (100) [010] et (010)[001]. Le premier est le système de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…Moreover, while the dominant LAM rotation axis in orthopyroxene ([010]; Figure e) and in clinopyroxene ([001]; Figure f) is consistent with former studies (Achenbach et al, ; Kaczmarek & Tommasi, ; Soustelle et al, ), their CPO geometry is incompatible with any known dislocation slip system. Indeed, the [001] axis corresponds to the Burgers vector in pyroxene (e.g., Bascou et al, ; Naze et al, ; Van Roermund & Boland, ; Zhang et al, ) and should therefore be observed subparallel to the lineation as in the majority of peridotitic natural shear zones (Achenbach et al, ; Kaczmarek & Tommasi, ; Soustelle et al, ). In contrast, the [001] axis of both orthopyroxene and clinopyroxene is systematically (Figure a), and consistently (Figure c), oblique to the foliation plane and even normal to it in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while the dominant LAM rotation axis in orthopyroxene ([010]; Figure e) and in clinopyroxene ([001]; Figure f) is consistent with former studies (Achenbach et al, ; Kaczmarek & Tommasi, ; Soustelle et al, ), their CPO geometry is incompatible with any known dislocation slip system. Indeed, the [001] axis corresponds to the Burgers vector in pyroxene (e.g., Bascou et al, ; Naze et al, ; Van Roermund & Boland, ; Zhang et al, ) and should therefore be observed subparallel to the lineation as in the majority of peridotitic natural shear zones (Achenbach et al, ; Kaczmarek & Tommasi, ; Soustelle et al, ). In contrast, the [001] axis of both orthopyroxene and clinopyroxene is systematically (Figure a), and consistently (Figure c), oblique to the foliation plane and even normal to it in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…Clinopyroxene CPO is more dispersed and thus hard to describe in detail ( Figures S1 and 7a). It is, however, noticeable that, as orthopyroxene, clinopyroxene [001] axis, which is also its main Burgers vector being thus generally located subparallel to the lineation (Naze et al, 1987;Steuten & Van Roermund, 1989;Van Roermund & Boland, 1981), is oblique to the foliation and even normal to it in the majority of analyzed samples (Figures 4f and 7a). In the more deformed rocks, mylonites, ultramylonites/UMB and some protomylonites, orthopyroxene, and clinopyroxene [001] axes are located close (<30°) to each other (Figure 7c).…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…5). This CPO suggests coherent deformation of the olivine and orthopyroxene, with dominant activation of the orthopyroxene (100)[001] slip system, which is the most commonly observed in naturally and experimentally deformed orthopyroxene (e.g., Naze et al, 1987;Nicolas and Poirier, 1976 Zaffarana et al, 2014), these correlations are still poorly understood; they might be related to crystallization and growth under deviatoric stress of, at least, part of the orthopyroxene crystals. Finally for some samples, no clear orthopyroxene CPO can be defined, suggesting that this mineral has crystallized after deformation.…”
Section: Orthopyroxenementioning
confidence: 99%
“…In the studied harzburgites, a tight correlation is observed between the olivine [100] and the orthopyroxene [001] axes and between the olivine [010] and the orthopyroxene [100] axes, respectively. Dislocation creep in orthopyroxene occurs through dominant activation of the (100)[001] slip system, the most common slip system observed in naturally and experimentally deformed orthopyroxene [e.g., Nazé et al , 1987]. During plastic deformation, the orthopyroxene [001] and [100] axes therefore tend to parallel the lineation and the pole of the foliation, respectively.…”
Section: Lattice‐preferred Orientationmentioning
confidence: 99%
“…Orthopyroxene LPO is characterized by a strong clustering of [100] and [001] axes. This LPO is accounted by the dominant activation of (100)[001], which is the easiest and the most common slip system observed in naturally and experimentally deformed orthopyroxene [ Nazé et al , 1987]. Interestingly, most samples display a significantly higher concentration of [100] axes than of the other axes and a tendency for the [001] axes to have a girdle distribution.…”
Section: Lattice‐preferred Orientationmentioning
confidence: 99%